Mini-DNA Barcode para autenticação de produtos de pescado processado - Glauber Batista Gois (2021)
Species substitution is a form of fish fraud for the main purpose of economic gain. DNA Barcode is a methodology that uses species-specific DNA sequence information for its identification. Previous work has established the usability of short Barcode DNA sequences for identifying specimens containing degraded DNA. This study aims to develop a mini-DNA Barcode method for 25 fish species commonly used in fish products in the region of Belo Horizonte, MG, Brazil. Four pairs of mini-DNA Barcode primers targeting short fragments of the cytochrome c oxidase I (COI) DNA barcode region were developed using several DNA sequences already deposited in universal databases. The method developed proved to be effective for identifying species in processed fish products.